Frequency of molecular response in a patient of chronic myeloid leukemia taking Tyrosine Kinase Inhibitors after 1 year of treatment Pakistan Institute of Medical Sciences experience - Soohn Jamil; Qasim Mehmood Buttar (Medical Journal of South Punjab, 2025)
Objective: To determine frequency of major molecular response in a patient of CML taking TKIs after 1 year of treatment PIMS experience Methodology: A descriptive cross-sectional study. Pakistan Institute of Medical Sciences (PIMS), Islamabad from 07-05-2024 to 07-11-2024. Current study included 121 patients by nonprobability consecutive sampling technique. Patients who didn’t follow up regularly and refused to participate in the study were excluded. After taking consent, age, gender and residential status were documented. Venous blood sample (3cc) was drawn and sent to the laboratory for the quantification of BCR-ABLI through mRNA GeneXpert to determine the major molecular response. Data was analyzed by SPSS 27. Descriptive statistics were applied for the age of patients to calculate mean and S.D. Frequencies were calculated for gender, age groups, residential status, and major molecular response. P value ? 0.05 was labelled significant. Results: Mean age of the patients was 44.21±11.64 years; and 73(60.3 %) were males and 48(39.7 %) were females. MMR was seen in 43.0% of the patients. MMR was seen in 34.5% of the patients in 18-35 years-group; in28.9 % of 36-50 years-group; and in61.7%of 51-60 years-group(p=0.004). Conclusion: TKIs have proven to be effective treatment choices for patients of CML, especially in older age groups.